Overview of the 70’s construction systems applied in the residential settlement “Aerodrom” - Skopje - Dimkov, Gjorgji; Nikolovski, Dobre; Papasterevski, Dimitar (TTEM, 2022)
The intensive housing construction in the Republic of North Macedonia, which began in the 1960s, especially after the catastrophic earthquake in Skopje in 1963, was based primarily on the huge development of the construction operation, whose power and opportunities could not be expressed only in Macedonia, but with great success was carried out with the largest construction operations in the former: SFR Yugoslavia, Czechoslovakia, USSR; as well as in Germany, the Arab countries: Algeria, Iran, Iraq, Egypt and others. According to the approved new urban plan of the city of Skopje, the most intensive building construction in Macedonia started in the seventies. New residential settlements emerged (Karpoš, Železara, Kisela Voda, etc.), which on a large scale began to give the physiognomy of the city. Also, the construction of the central city area with social, administrative and residential buildings started even more intensively (according to the project of the Japanese architect Kenzo Tange), designated as “city wall” and “city gates”. The growth and expansion of the city on a daily basis pressured the management structures, among others smaller ones, to start building the largest residential complex “Aerodrom”. The buildings were built with inflexible technologies (with large surface and tunnel plates), where the possibility of changing the organization of the apartments is excluded, which was not the case with the buildings built with classical skeletal systems. This paper aims to give an overview of the applied construction systems and technologies of construction and the correlation between the structure and the construction of the apartment and the structure of the family in the residential buildings from the settlement “Aerodrom” in Skopje, built in 1977.
The task of this research is to make a brief analysis of the basic urban plan towards the main project for the settlement “Aerodrom” in Skopje and analysis of the existing (built) condition, and the purpose of the research is to obtain knowledge about the characteristics of certain types of construction systems applied in residential buildings, as well as the characteristics of the technological systems of realization. Each of the systems applied in the settlement is analysed separately: – the system “REMO” of large surface plates with chairs, – the “REMO” system of tunnel plates and – the frame system, to complete this research by comparing all the previously mentioned systems in terms of construction dynamics. Several scientific research methods have been used to design this study according to the nature of the problem and the field of research: analysis, own field research, comparison, synthesis of the results. The research was performed with the help of data obtained from the operational plans for the implementation of the neighbourhood units and the technical documentation for them. After the synthesis and comparative analysis of the data collected and the results of the analyses, the basic principles and conclusions were announced at the end of the paper, as a good basis for possible future similar research.
Keywords: construction systems, technologies of construction, residential settlement, “Aerodrom” – Skopje